2014
DOI: 10.1016/j.drugalcdep.2014.09.771
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, negative urgency and substance use initiation in adolescents

Abstract: Background Studies show depressive symptoms are associated with substance use in adolescents, but the mechanism underlying this association is still unclear. This study investigated negative urgency – the disposition to rash action during emotional states – as a factor explaining relations between depressive symptoms and use of several substances. Methods In this cross-sectional study, 476 adolescents (mean age 14.5 years) completed self-report surveys. Regression models and products of coefficient analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 35 publications
4
42
1
2
Order By: Relevance
“…It follows that negative family dynamics would have to increase negative emotional symptoms in adolescents for SU risk to increase. However, as we anticipated in the hypothesis, we found no single mediation of negative emotional symptoms on SU as reported in other studies (Guzmán et al, 2011;McCarty et al, 2012;Pang, Farrahi, Glazier, Sussman, & Leventhal, 2014;Scholes-Balog, Hemphill, Patton, & Toumbourou, 2015). Instead, our findings show that such symptoms increase sensation seeking, which in turn affects substance use.…”
Section: Discussioncontrasting
confidence: 67%
“…It follows that negative family dynamics would have to increase negative emotional symptoms in adolescents for SU risk to increase. However, as we anticipated in the hypothesis, we found no single mediation of negative emotional symptoms on SU as reported in other studies (Guzmán et al, 2011;McCarty et al, 2012;Pang, Farrahi, Glazier, Sussman, & Leventhal, 2014;Scholes-Balog, Hemphill, Patton, & Toumbourou, 2015). Instead, our findings show that such symptoms increase sensation seeking, which in turn affects substance use.…”
Section: Discussioncontrasting
confidence: 67%
“…Each study measure described below has shown good psychometric properties in previous adolescent samples (Audrain-McGovern et al, 2004; Bastiani et al, 2013; Eaton et al, 2010; Johnston et al, 2015; Leventhal et al, 2015 in press; Martino, Grilo, & Fehon, 2000; Muris & Meesters, 2008; Pang, Farrahi, Glazier, Sussman, & Leventhal, 2015 in press; Wagner et al, 2006; White & Labouvie, 1989). Unless otherwise specified, a mean score per item composite was calculated and composites were scored such that higher scores reflect higher psychopathology.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the transdiagnostic phenotype measures described below has been consistently associated with multiple psychopathologies (Audrain-McGovern et al, 2009; Audrain-McGovern et al, 2004; Cyders et al, 2007; Ellis & Rothbart, 2001; Isolan, Salum, Menezes Flores, de Carvalho, & Gus Manfro, 2012; Leventhal et al, 2015 in press; Leyro, Zvolensky, & Bernstein, 2010; Muris et al, 2008; Muris, Schmidt, Merckelbach, & Schouten, 2001; Pang et al, 2015 in press; Smith et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…There is preliminary evidence that negative urgency is associated with marijuana use (e.g., Pang et al, 2014;Robinson et al, 2014) and negative marijuana consequences (e.g., Churchwell et al, 2010). Lack of planning has been robustly associated with adolescent marijuana use and frequency in some studies (e.g., Xiao, 2008;Castellanos-Ryan et al, 2013) but unrelated in other studies (e.g., Kong et al, 2013;Leeman et al, 2014).…”
Section: Separable Impulsivity Traits: the Upps-p Modelmentioning
confidence: 99%